Distinctively different: A new approach to valuing architectural amenities - Gabriel Ahlfeldt; Nancy Holman (European Regional Science Association (ERSA), 2015)
We propose a method to estimate the capitalized value of the architectural design quality of a neighbourhood. Our economic design premium is identified by spatially differentiating property prices and design quality within neighbourhoods and comparing the differences across neighbourhoods. We apply our method to 47 conservation area neighbourhoods in England in which we analyse around 7900 property transactions and interview more than 500 residents. We find a capitalization effect of about 25.4% (38.7k) associated with a one-step increase on a five-step scale ranging from not at all-distinctive to very distinctive. Our results suggest that this effect is at least partially driven by an architectural externality.
Keywords: R52; D23; C7; 330; Architecture; beauty; boundary discontinuity; conservation areas; design; Englan